Konsep Kafa'ah: Studi Pandangan Habaib di Kabupaten Jember - Aba Fahmi Roby (Rechtenstudent, 2020)
In a marriage, in addition to the terms and conditions that affect whether or not a marriage is legal, there are other rules, including the concept of kafa'ah. Kafa'ah, namely equality between prospective husbands and future wives in various matters including religion (din), descent (nasab), position (hasab) and the like. The term kafa'ah is also known among the Habaib in Jember Regency. Habaib circles, especially in Jember, set specific criteria for the concept of kafa'ah. The existence of the concept of kafa'ah then gave birth to differences of opinion among the Habaib in Jember Regency. This study used a descriptive qualitative research approach, primary data sources were obtained from individuals or individuals such as interviews, while secondary data sources were obtained from scientific publications in the form of books, books, theses, journals, previous research, and related articles. The data source was obtained using interviews and documentation. The data obtained were analyzed using the empirical normative method and tested for its validity by triangulation. The result is a conclusion that a Syarifah is required and attempted to marry Habaib because he is considered sekufu 'as both descendants of the Prophet SAW. Even among some Habaib in Jember Regency that kafa'ah is included in the category of rukun marriage. So that the conclusion that Syarifah married a man not descended from Habaib, apart from being able to break her lineage, also had its social impact.